2017
DOI: 10.1080/00071668.2017.1315051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermented cottonseed meal on the growth performance, gastrointestinal microflora population and small intestinal morphology in broiler chickens

Abstract: 1. This experiment was conducted to evaluate the effects of replacing dietary cottonseed meal (CSM) or fermented cottonseed meal (FCSM) for soya bean meal (SBM) on growth performance, carcass characteristics, gastrointestinal microbial populations, and intestinal morphology of broiler chickens. 2. CSM was fermented with Bacillus subtilis, Aspergillus niger and A. oryzae for 7 d. A total of 300 one-d-old male Ross 308 broiler chickens were used in a 42-d experiment in which the birds were randomly allotted to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 29 publications
5
61
0
Order By: Relevance
“…They indicated that these substances could stimulate the proliferation of lactobacilli species. Meanwhile, BAS spores are capable of providing an anaerobic environment for the growth and proliferation of lactobacilli species by uptaking the oxygen present in the gut after germination (Jazi, Boldaji, Dastar, Hashemi, & Ashayerizadeh, ). In addition, BAS disturbs the growth of pathogens by synthesizing antimicrobial substances including amicoumacin, bacilysin, bacillaene, bacillomycins, and bacteriocin‑like substances (Suva et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that these substances could stimulate the proliferation of lactobacilli species. Meanwhile, BAS spores are capable of providing an anaerobic environment for the growth and proliferation of lactobacilli species by uptaking the oxygen present in the gut after germination (Jazi, Boldaji, Dastar, Hashemi, & Ashayerizadeh, ). In addition, BAS disturbs the growth of pathogens by synthesizing antimicrobial substances including amicoumacin, bacilysin, bacillaene, bacillomycins, and bacteriocin‑like substances (Suva et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cottonseed meal (CSM) is an agroindustrial byproduct of the oil industry with high protein content and has a great potential of being used as a protein source (Gao, Cao, & Hi, ). Because of the high concentrations of gossypol, an antinutritional compound, CSM, has been used only for ruminant feed (Berardi & Goldblatt, ; Martinez, Berardi, & Goldblatt, ) or fermented for broiler chickens (Jazi, Boldaji, Dastar, & Hashemi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high concentrations of gossypol, an antinutritional compound, CSM, has been used only for ruminant feed JFDS-2019-0723 Submitted 5/13/2019, Accepted 7/19/2019. (Berardi & Goldblatt, 1969;Martinez, Berardi, & Goldblatt, 1970) or fermented for broiler chickens (Jazi, Boldaji, Dastar, & Hashemi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Chao1 value is often used to estimate the total number of species in a sample, while Shannon indicates the α-diversity of intestinal microflora. The higher the Shannon is, the more evenly the distribution of microflora species is (22) . As depicted in Fig.…”
Section: (A)mentioning
confidence: 99%
“…The regulation of gut microbiota (GM) has become an important way for humans to treat gastrointestinal and metabolic diseases (20) , and it plays an important role in the intestinal morphology, immunity, digestion and health of the host (21,22) . A healthy GM ecology is critical for the establishment of tissue homeostasis health.…”
mentioning
confidence: 99%